2009
DOI: 10.1007/s11307-009-0212-5
|View full text |Cite
|
Sign up to set email alerts
|

Potential of Dual Time Point FDG-PET Imaging in Differentiating Malignant from Benign Pleural Disease

Abstract: There is an increasing uptake of (18)F-FDG over time in pleural malignancies, whereas the uptake in benign pleural disease generally stays stable or decreases over time. Therefore, dual time point imaging appears to be an effective approach in differentiating benign from malignant pleural disease, which increases the sensitivity and is also helpful in guiding the biopsy site for a successful diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
39
0
7

Year Published

2009
2009
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 31 publications
1
39
0
7
Order By: Relevance
“…In fact, as observed by the authors of the present study [1], some tumour cells of mesothelioma continue to take up glucose longer than 90 min after tracer injection and require several hours to reach maximum level in FDG uptake. Therefore, if the second PET is acquired at 90 min from injection, some lesions could be lost.…”
supporting
confidence: 78%
See 3 more Smart Citations
“…In fact, as observed by the authors of the present study [1], some tumour cells of mesothelioma continue to take up glucose longer than 90 min after tracer injection and require several hours to reach maximum level in FDG uptake. Therefore, if the second PET is acquired at 90 min from injection, some lesions could be lost.…”
supporting
confidence: 78%
“…I n the study by Mavi and co-workers from Dr. Alavi's group, published in the present issue of Molecular Imaging & Biology [1], the authors reported their experience with the 18F-fluorodeoxyglucose positron emission tomography (FDG-PET) in malignant pleural mesothelioma patients (MPM). In particular, they have focused their attention on the diagnostic phase of this disease that is still a challenge in all its aspects: diagnosis, staging and therapy [2].…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…MPM olgularında FDG PET-BT ile geç görüntüleme esnasında azalan Standardize Tutulum Değerleri'nin (SUV) saptanmasının benign karakterdeki lezyonlar açısından anlamlı olabileceği konusunda görüş birliği olmakla birlikte, artan ya da sebat eden SUV değerle-rinin ayırıcı tanıya katkısı ise tartışmalıdır (43)(44)(45).…”
Section: Plevral Mali̇gni̇telerunclassified